Outcomes in IVF Conceived Pregnancies Complicated with Hypertensive Disorders - Vuniqi-Krasniqi, Merita; Daka, Qëndresë (Journal of Nepal Paediatric Society, 2018)
Introduction: Many studies have demonstrated an increased risk of obstetrical and neonatal complications after assisted reproductive techniques treatment compared to spontaneously conceived pregnancies. There are no data regarding these outcomes in Kosovo. The aim of our study was, to compare maternal, obstetric and neonatal parameters of in-vitro fertilization (IVF) conceived pregnancies complicated with hypertensive disorders (HD) versus uncomplicated spontaneous conceived pregnancies in Kosovo. Material and Methods: This observational study was undertaken at the Department of Gynaecology, University Clinical Centre of Kosova, during a two year period. A total of 104 pregnant women were included in the study. Maternal, obstetrical and neonatal parameters in both groups were assessed and compared. Statistical analysis was performed using SPSS 22.0 statistical software. Results: that conceived through IVF and had HD during pregnancy were older (p=0.0001), primipara (p=0.007), had multiple pregnancies (p=0.0001) and had worse obstetrical outcomes including cervix insufficiency (p=0.0001), premature rupture of membranes (p=0.0001), and delivery type (p=0.003) compared to women that conceived spontaneously. The only statistically significant differences in neonatal outcomes were in the Apgar1st (p=0.012) and Apgar5th (p=0.004) scores that were higher among babies born from mothers that conceived through IVF and had HD during pregnancy. Conclusions: Results of our study are in line with the results from other countries in regards to maternal demographic profile, except education level and employment, and obstetrical outcomes. However, there were no differences in regards to neonatal outcomes between the two groups of babies other than in the Apgar 1st and Apgar 5th scores.